Distribution and sources of polycyclic aromatic hydrocarbons in surface sediments from the Bering Sea and western Arctic Ocean. Issue 1 (15th March 2016) - Zhao, Mengwei; Wang, Weiguo; Liu, Yanguang; Dong, Linsen; Jiao, Liping; Hu, Limin; Fan, Dejiang
Abstract: To analyze the distribution and sources of polycyclic aromatic hydrocarbons (PAHs) and evaluate their potential ecological risks, the concentrations of 16 PAHs were measured in 43 surface sediment samples from the Bering Sea and western Arctic Ocean. Total PAH (tPAH) concentrations ranged from 36.95 to 150.21 ng/g (dry weight). In descending order, the surface sediment tPAH concentrations were as follows: Canada Basin > northern Chukchi Sea > Chukchi Basin > southern Chukchi Sea > Aleutian Basin > Makarov Basin > Bering Sea shelf. The Bering Sea and western Arctic Ocean mainly received PAHs of pyrogenic origin due to pollution caused by the incomplete combustion of fossil fuels. The concentrations of PAHs in the sediments of the study areas did not exceed effects range low (ERL) values. Highlights: The concentrations of PAHs in the sediments of the Bering Sea and western Arctic Ocean did not exceed the effects range low. Fuel combustion was the primary source of PAHs in the surface sediments of the Bering Sea and the western Arctic Ocean. The distribution and migration of PAHs in marine sediments of study areas are affected by different factors.